ANALISIS PENTINGNYA PENILAIAN PRESTASI KERJA DALAM HUBUNGANNYA DENGAN PENINGKATAN MOTIVASI KARYAWAN - Okky Chandra (Center for Economic Studies Universitas Katolik Parahyangan, 2001)
Performance appraisal is one of many aspects that are very important in Human resource management. On the other hand, motivation is also vital for a Manager because it drives and directs all human behavior, including an employee's performance. This short essay tries to analyze the relationship Between performance appraisal and motivation, and how performance appraisal system can enhance motivation of employees. The motivation itself is seen in the light of content and Process theories